A Review Paper on: Design and Development of Volunteer Based Artificial Intelligent Powered Post Accident Alert System - Dr. Pushparani M K; Divya V S; Pavitra; Saika K; Shreelaxmi J Wadi (International Research Journal on Advanced Engineering Hub (IRJAEH), 2025)
In current scenario the mobility of vehicles increases in the proportion of the population. Due to the traffic congestion, the accidents are also increasing day by day. This causes the loss of life or traumatic injuries and disfigurements due to the delay in the arrival of ambulances to the accident spot or from the accident spot to the hospital. The main idea is to build an application that makes adoption of the smart phones, embedded system and Artificial Intelligence. For detecting any collision if there is a sudden external disturbance in the speed with the help of the Sensors based Algorithm will act. The application continually reads the data from the smartphone’s sensors and sends the data to the cloud. If the alert message is unattended for more than 10 seconds, the” request for help” message will be sent to the volunteers, Ambulance, police and family members. The proposed system comprises two phases: Accident detection and Notification phase. For the accident detection phase, a smartphone application has been fully implemented. For the notification phase whenever an accident occurs, the website receives the information regarding the accident. The website shows the details of the accident such as the information of driver and vehicle. A web-based system has been implemented for use by hospitals. The programming part is an Android application introduced in drivers Smartphones which is used to get the location point by point based on longitudes and latitudes.